Keberadaan Obligasi Syari’ah di Indonesia: Peluang dan Tantangannya - Bachruddin Bachruddin (Unisia, 2008)
The role of syari’ah obligation (sukuk) has been prospective, due to the fact that at presentpeople may own certificates of obligation without having to own huge amount of money.Nevertheless, investors must remain to be careful before deciding to invest in this area ofbusiness. This is due to the fact that apart from being new area, the issuance of sukuk isalso still dominated by the conventional issuers. Therefore, Moslems who want to investshould consider: the agreements between investors and the issuers of sukuk; the backgroundof the issuers of sukuk, whether they are feasible or not. This is important inrelation to the return that will be gained by investors, in order for them not to be trapped by“bodong” investment, appearing recently.Keywords: syari’ah obligation, careful, feasible, investment.